The Use of Insecticides Viewed from a Technical View of Applications in Corn Crops: Case Study of Corn Farmer Behavior - Arfan Arfan; Sri Sudewi; Mukhlis Mukhlis; Mismawarni Srima Ningsih (Jurnal Penelitian Pendidikan IPA, 2024)
Synthetic insecticides are still used as the main solution in suppressing herbivorous insect attacks on maize at the farm level. The purpose of this research is to determine and find new ways farmers use insecticides wisely through a multi-aspect approach. The method used to determine the sample was purposive sampling with 50 corn farmers spread across five villages in the Tambulava sub-district. Primary data collection was obtained by observation through direct interviews with corn farmers using a prepared semi-structured questionnaire, and secondary data were obtained through a literature study and various sources related to research issues. Quantitative data were analyzed by simple tabulation (cross-tabulation analysis), while qualitative data were analyzed using an interpretation of existing phenomena. The results showed that four herbivorous insect species attacked corn plants in the Tanambulava District: Spodoptera frugiperda, Helicoverva armigera, Ostrinia furnacalis, and Locusta sp. Insecticide application time by local farmers is generally done in the morning by 90%, with application frequency varying 1-3 times a week. There are 13 active insecticide ingredients used by corn farmers in Tambulava District, Sigi Regency.